AN ANALYSIS OF POLITENESS MAXIMS USED BY THE MAIN CHARACTERS IN ME BEFORE YOU MOVIE - Putri Muhaling; Sanerita T. Olii; Paula L. Hampp (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study aims to analyze the maxims of politeness used by the main characters in the film Me Before You. The research method used is qualitative method. In analyzing the data, the writer used the theory of politeness maxims from Geofrrey Leech (1983). There are 6 kinds of politeness maxims proposed by Leech, namely: Tact Maxim, Generosity Maxim, Modesty Maxim, Approbation Maxim, Agreement Maxim and Sympathy Maxim. The data in this study were taken by the main characters utterances in Me Before You movie, Louisa and William. The result of this research is that there are 27 politeness maxims used by the main characters in this movie. All kinds of politeness maxims are used by the main characters, 3 Tact Maxim, 6 Generosity Maxim, 3 Modesty Maxim, 8 Approbation Maxim, 5 Agreement Maxim, and 2 Sympathy Maxim. The most dominant kinds of maxim used in the movie is Approbation Maxim. The most dominant maxim used by Louisa is Generosity Maxim and the most dominant maxim used by William is Approbation Maxim.